Estimating and scaling-up biomass and abundance of epi- and infaunal bivalves in a Swedish archipelago region: Implications for ecological functions and ecosystem services - Greeve, Youk; Bergström, Per; Strand, Åsa; Lindegarth, Mats (Frontiers in Marine Science, 2023)
Introduction As suspension-feeders, bivalves play a key role in maintaining regulatory functions of coastal ecosystems, which are linked to important ecosystem services. The functions attributed to bivalves depend on the life habits of a species (epi- or infauna) and their abundance and biomass. To properly quantify and assess these functions, detailed information the distribution, abundance and biomass at the ecosystem scale is critical. Amongst others, this requires an understanding on how environmental conditions shape special patterns in distribution. In this study we investigate this fundamental information on the Swedish west coast, an area where this information is lacking. Methods A survey which was designed to representatively sample both epi- and infaunal bivalves from randomized locations in various habitat types was conducted. Specifically, abundance and biomass of all species were recorded in the intertidal (0-0.5 m) and the shallow subtidal zone (0.5-2 m). The sites were distributed over an offshore gradient and at two exposure levels. This sampling structure allowed to extrapolate the results to an ecosystem level though information on the areal extent of these habitats using GIS layers. Results It was found that even though there exist a great variability among sites, in general epifaunal bivalves outweigh infaunal bivalves approximately 3 to 1. In terms of abundance, the ratio is more or less reversed and infaunal species occur in greater numbers. Most bivalves were found at an intermediate level of exposure, but due to the areal extend of the sheltered inner-archipelago this was the most important habitat for bivalve abundance and biomass. It was also found that invasive epifaunal oyster Magallana gigas and the invasive infaunal clam Ensis leei both dominated their respective groups in terms of biomass. Discussion Though the survey was relatively small, these results serve as a valuable insight of the relative importance of epi- and infaunal bivalves in this region. This gives understanding on which species and habitats are particularly important for ecosystem functions and services related to bivalves. This also provide a starting baseline for attempts to quantify ecosystem services provided by certain species or groups of bivalves in the future.